PENINGKATAN HASIL BELAJAR PADA MATA PELAJARAN PKN MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT FACILITATOR AND EXPLAINING DI KELAS V SDN 02 TALAWI HILIR - Maryulis Maryulis (STKIP Pesisir Selatan, 2020)
Based on Student Learning Outcomes of Class V SDN 02 Talawi Hilir in PKN Subjects it was found that Student Learning Outcomes in PKN Subjects was still very low. The purpose of this study was to describe and obtain information about Student Learning Outcomes Improvement in PKN Subjects through the cooperative learning model type Student Facilitator and Explaining in Class V SDN 02 Talawi Hilir. This research is a class action research. Research procedures in this study include planning, action, observation and reflection. This research consisted of two cycles with four meetings. The research subjects consisted of 29 students of Class V SDN 02 Talawi Hilir. Research data were collected using Observation sheets. Data were analyzed using percentages. Based on the results of the research and discussion that has been presented in the previous chapter, it can be concluded that it can be concluded that the model of demonstration learning can improve student learning outcomes in the subjects of the National Education School in Class V SDN 02 Talawi Hilir. Student Learning Outcomes from cycle I to cycle II. Student learning outcomes in the first cycle was 73.79 (enough) increased to 82.76 (good) with an increase of 8.97 (good).